Synthetic strategies for the fluorescent labeling of epichlorohydrin-branched cyclodextrin polymers - Malanga, Milo; Bálint, Mihály; Puskás, István; Tuza, Kata; Sohajda, Tamás; Jicsinszky, László; Szente, Lajos; Fenyvesi, Éva (Beilstein Journal of Organic Chemistry, 2014)
The fluorescent tagging of cyclodextrin derivatives enlarges their spectroscopic properties thus generating chemosensors, biological tools for visualization and sophisticated photoresponsive devices. Cyclodextrin polymers, due to the cooperative interactions, exhibit additional properties compared to their monomeric counterpart. These macromolecules can be prepared either in well water-soluble form or as gels of high swelling. Two versatile synthetic strategies for introducing a fluorescent tag (rhodamine, fluorescein, nitrobenzofuran or coumarin) into the water-soluble epichlorohydrin branched cyclodextrin polymers were worked out and compared. The fluorescent labeling was realized in three steps: 1) building in azido moieties, 2) transforming the azido groups into amino groups and 3) coupling the proper fluorescent compound to the amino groups. The other strategy started by functionalization of the monomer prior to the branching. Either the fluorescent-labeled monomer or the intermediate azido derivative of the monomer was branched. Further tuning of the properties of the polymer was achieved via branching of the methylated cyclodextrin derivative. The key intermediates and the fluorescent final products were characterized by various spectroscopic techniques and capillary electrophoresis. The applied synthetic routes were evaluated based on the molecular weight, cyclodextrin content of the products and the efficiency of labeling.
Keywords: coumarin; fluorescein; functionalized monomers and polymers; nitrobenzofurazan; rhodamine

Cyclodextrin Technology - Szejtli, J. (Kluwer, 1998)

(untitled) - Loftsson, T.; Brewster, M. E. (J. Pharm. Sci., 1996)

(untitled) - Arima, H.; Hirayama, F.; Okamoto, C. T.; Uekama, K. (Recent Res. Dev. Chem. Pharm. Sci., 2002)

(untitled) - Zhang, J.; Ma, P. X. (Adv. Drug Delivery Rev., 2013)

Cyclodextrins - Jicsinszky, L.; Fenyvesi, E.; Hashimoto, H.; Ueno, A. (Cyclodextrin derivatives, 1996)

(untitled) - Gref, R.; Duchene, D. (J. Drug Delivery Sci. Technol., 2012)

(untitled) - Wiedenhof, N.; Lammers, J. N. J. J.; van Panthaleon Van Eck, C. L. (Staerke, 1969)

(untitled) - Harada, A.; Furue, M.; Nozakura, S. (Polym. J., 1981)

Proceedings of the first International Symposium on Cyclodextrins - Fenyvesi, E.; Szilasi, M.; Zsadon, B.; Szejtli, J.; Tudos, F. (Water-soluble cyclodextrin polymers and their complexing properties, Budapest 1981, 1982)

(untitled) - Gidwani, B.; Vyas, A. (Colloids Surf., B, 2014)

(untitled) - Van de Manakker, F.; Vermonden, T.; van Nostrum, C. F.; Hennink, W. E. (Biomacromolecules, 2009)

(untitled) - Yang, S. Y.; Hoonor, R.; Jin, H.-S.; Kim, J. (Bull. Korean Chem. Soc., 2013)

(untitled) - Gil, E. S.; Li, J.; Xiao, H.; Lowe, T. L. (Biomacromolecules, 2009)

(untitled) - Favier, I. M.; Baudelet, D.; Fourmentin, S. (J. Inclusion Phenom. Macrocyclic Chem., 2011)

(untitled) - Zohrehvand, S.; Evans, C. H. (Polym. Int., 2005)

(untitled) - Ncube, P.; Krause, R. W. M.; Mamba, B. B. (Phys. Chem. Earth, 2014)

(untitled) - Khan, A. R.; Forgo, P.; Stine, K. J.; D’Souza, V. T. (Chem. Rev., 1998)

(untitled) - Ashton, P. R.; Königer, R.; Stoddart, J. F.; Alker, D.; Harding, V. D. (J. Org. Chem., 1996)

(untitled) - Sun, T.; Zhang, H.; Kong, L.; Qiao, H.; Li, Y.; Xin, F.; Hao, A. (Carbohydr. Res., 2011)

(untitled) - Hasegawa, T.; Kondo, Y.; Koizumi, Y.; Sugiyama, T.; Takeda, A.; Ito, S.; Hamada, F. (Bioorg. Med. Chem., 2009)

(untitled) - Scriven, E. F. V.; Turnbull, K. (Chem. Rev., 1988)

(untitled) - Jicsinszky, L.; Iványi, R. (Carbohydr. Polym., 2001)

(untitled) - Hbaieb, S.; Kalfat, R.; Chevalier, Y.; Amdouni, N.; Parrot-Lopez, H. (Mater. Sci. Eng., C, 2008)

(untitled) - Malanga, M.; Jicsinszky, L.; Fenyvesi, É. (J. Drug Delivery Sci. Technol., 2012)

(untitled) - Brady, B.; Lynam, N.; O’Sullivan, T.; Ahern, C.; Darcy, R. (Org. Synth., 2000)

(untitled) - Zhao, H.; Zhang, J.; Gao, F.; Lan, M. (Adv. Sci. Lett., 2010)

(untitled) - Ghosh, P. B.; Whitehouse, M. W. (Biochem. J., 1968)

(untitled) - Mourtzis, N.; Paravatou, M.; Mavridis, I. M.; Roberts, M. L.; Yannakopoulou, K. (Chem. – Eur. J., 2008)

(untitled) - Ueno, A.; Suzuki, I.; Osa, T. (Anal. Chem., 1990)